Effects of Replacing Peanut Seed Cake with Brewery Dried Yeast on Laying Performance, Egg Quality and Carcass Characteristics of Rhode Island Red Chicken - Girma, Meseret; Tamir, Berhan; Dessie, Tadelle (International Journal of Poultry Science, 2011)
One hundred and eighty 26-week old Rhode Island Red chicken were used to determine the performance, fertility, hatchability and economic of chicken fed with ration containing Peanut Seed Cake (PSC) and Brewery Dried Yeast (BDY). The treatments were T1 (20% PSC + 0% BDY), T2 (15% PSC + 5% BDY), T3 (10% PSC + 10% BDY), T4 (5% PSC + 15% BDY), T5 (0% PSC + 20% BDY) and T6 as control (commercial layer’s ration) and the experiment lasted for 12 weeks. The experiment was arranged in a Completely Randomized Design (CRD) with six treatments, each replicated two times with 15 birds per replicate. Hens were individually weighed at the start and end of the experiment. Data on Dry Matter Intake (DMI), Hen Day Egg Production (HDEP), egg weight and were recorded daily. Egg quality parameters were determined at an interval of 3 days on 6 eggs per replicate. The chemical analysis showed that BDY contained 41.2% CP and 2982.04 kcal ME/kg DM and PSC 42.2% CP and 2842.5 kcal ME/kg DM, indicating their potential to be used as sources of both protein and energy in poultry feeding. DMI of birds on T3 and T4 were similar with that of birds on control diet, but diet T5 resulted in significantly increased DMI than control diet. Diets T1 and T2 resulted in a significantly (p